Hubungan Perkembangan Bahasa Anak Usia 5-6 tahun terhadap Kesiapan Sekolah Dasar - Handayani, Oktarina Dwi; Permadhy , Arselia Meidinda (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2026)
This study aims to analyze the relationship between language development and school readiness in children aged 5–6 years before entering formal education. The study used a quantitative approach with a correlational design. The study subjects were 156 children enrolled in kindergartens in East Jakarta. Data were collected through language development and school readiness assessment instruments, then analyzed using the Spearman correlation test with the help of the SPSS program. The results showed a strong and significant relationship between language development and school readiness. Children with more developed language skills tend to show better readiness in early academic aspects, adaptation to the school environment, and participation in group activities. These findings confirm that language development is an important factor in supporting children's readiness to enter formal education. Therefore, optimal language stimulation is needed from an early age through the active role of parents and educators to maximize children's school readiness.